The Relationship between the Intensity of Tahajud Prayer and the Stress Level of Medical Students of Muhammadiyah University of Malang, Class of 2021 - Iwan Sis Indrawanto; Dewi Ritna Ningrum; Kusuma Andriana; Ikwan Handi Rosiyanto (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
Stress can be defined as a condition or feeling that occurs when a person feels that his or her demands exceed the resources that he or she has, resulting in a gap between the demands of daily life and the person's ability to respond to them An obvious imbalance exists. Research has found that medical students, especially first-year medical students, experience high levels of stress due to the life change from high school to college. Sustained stress can trigger memory and cognitive impairment, gastrointestinal disorders, reduced immunity, and cardiovascular system disease. Tahjud prayers, if performed seriously and consistently, can produce positive emotional responses and increase the effectiveness of stress management. The purpose of this study was to determine the relationship between Tahajud prayer intensity and stress levels among medical students at Muhammadiyah University, Malang. This study used an analytical observational design with a cross-sectional approach. This study adopted the total sampling technique with a sample size of 94. Data on stress levels were collected using the Depression, Anxiety and Stress Scale (DASS-42) and the Tahajud Prayer Intensity Questionnaire through validation testing. The results showed that the intensity of Tahajud prayer was low for 51 respondents (54.3%) and moderate for 48 respondents (51.1%). There is a significant relationship between the intensity of Tahajud prayers and stress levels among students at the Faculty of Medicine at Muhammadiyah University.